HIV treatment as prevention among men who have sex with men in the UK: is transmission controlled by universal access to HIV treatment and care?. Issue 9 (28th July 2013) - Brown, AE; Gill, ON; Delpech, VC
<x xml:space="preserve">Abstract</x> Objectives In the UK, free HIV care is provided through dedicated HIV clinics. Using the national cohort of men who have sex with men (MSM) with diagnosed HIV infection and estimates of the number of undiagnosed men, we assessed whether high retention in HIV care and treatment coverage is sufficient to reduce HIV transmission. Methods Antiretroviral therapy (ART) uptake and viral load distribution among diagnosed men were analysed by treatment status and CD4 count for the period between 2006 and 2010. A multi‐parameter evidence synthesis (MPES) method was used to estimate the size of the undiagnosed population. The viral load distribution among newly diagnosed untreated men was applied to the undiagnosed population. Infectivity was defined as a viral load > 1500 HIV‐1 RNA copies/mL. Results Between 2006 and 2010, ART coverage among all HIV‐infected MSM (diagnosed and undiagnosed) increased from 49 to 60%, while the proportion of infectious men fell from 47 to 35%. Over the same period, the number of all HIV‐infected MSM increased from 30 000 to 40 100 and the number of infectious MSM remained stable at 14 000. Of the 14 000 infectious MSM in 2010, 62% were undiagnosed, 33% were diagnosed but untreated, and 5% received ART. Extending ART to all diagnosed HIV‐infected MSM with CD4 counts < 500 cells/μL in 2010 would have reduced the overall proportion of infectious men from 35 to 29% and halving the proportion who were undiagnosed would further have reduced this to 21%. Conclusions High ART coverage in the UK has reduced the infectivity of the HIV‐diagnosed population. However, the effectiveness of treatment as prevention will be limited unless the undiagnosed population is reduced through frequent HIV testing and consistent condom use.